Influence of hall current on oscillatory Couette flow in the presence of an inclined magnetic field through porous medium - Khan , Masood; Saeed, Saira; Fetecau, C.; Azram, Mohammad (Begell House, Inc., 2014)
The aim of this paper is to construct an exact solution corresponding to the oscillatory Couette flow in a rotating system. An incompressible viscous fluid occupies the porous medium in a rotating horizontal parallel-plate channel subject to a uniform strength, static, oblique magnetic field acting at an angle Θ to the positive direction of the axis of rotation. The flow is generated by the nontorsional oscillations of both plates. Hall effects are taken into account and an exact solution is obtained by using the Laplace transform technique. Moreover, asymptotic behavior of the obtained solution is also analyzed for several cases. The effects of the pertinent parameters such as the Hall current parameter (m), rotation parameter (K2), Hartmann number (M2), Darcy number (Da), and magnetic field inclination (Θ) on the velocity profiles are graphically depicted and studied in detail.